Reconsidering macroeconomic policy prescriptions with meta-analysis - Sebastian Gechert (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2022)
This paper investigates recent developments in meta-analysis, the tool to quantitatively synthesize research in a certain body of literature. After providing a brief overview on how to do a meta-analysis and discussing recent methodological advancements in the field, I review applied contributions to the field of macroeconomics. It turns out that meta-analyses have often questioned the conventional wisdom and established new consensuses in fiscal, monetary and labor market policies by uncovering substantial publication bias and unexpected determining factors in many bodies of literature – in particular those dominated by policy conclusions in the neoclassical tradition like minimum wages, financial regulation and the relative effects of tax and spending policies.
Keywords: E50; E60; J30; 330; Meta-analysis; macroeconomics; monetary policy; fiscal policy; labor market